Traditional and modern models of family education in China - Afanasyeva, Tatsiana S. (University Pedagogical Journal, 2024)
The genesis of family education in China is described. The prerequisites for its reform at the present stage are defined. The most widespread models of traditional upbringing are presented and critically analysed. The problems of family upbringing caused by internal migration of rural population are revealed. The main tendencies of modern educational strategy are characterised.
Keywords: family education; models of family education; cultural tradition of education